CRIMINAL REGULATORY REFORM TO ERADICATE PROSTITUTION PRACTICES - Assyifa, Lilia Safitri; Sitaputri, Kamila Maharani; Indradjaja, Nobella; Chamdani, Chamdani (EQUALEGUM International Law Journal, 2024)
Background. The rapid technological advancement accelerates the spread of various forms of information, including information regarding prostitution practices. Meanwhile, from a legal perspective, a complete regulation of prostitution practices is at its minimum. The impacts of prostitution practices affect health aspects and drive social turmoil in the community. This research aims to review regulations related to prostitution practices, especially in the applicable criminal law in Indonesia, and propose factors that emphasize a law reform, so that in the future, prostitution practices may be handled more thoroughly. Research Method. This research uses a normative method, with secondary data that includes literary research, reviews on laws and regulations, and an analysis method that uses a prescriptive technique. Findings. In reality, several regional regulations have regulated prostitution practices, but nationally, there has not been any regulation that strictly regulates prostitution practices. Conclusion. In a preventive and repressive form, which are clear limitations of prostitution practices, criminal act reform for pimps, criminalization for commercial sex workers, the use of the double-track system in imposing sanctions, criminal act formulation, and criminal aggravation.